PELATIHAN KETERAMPILAN SENI MENGHIAS MEDIA DENGAN TEKNIK DECOUPAGE ART PADA KELOMPOK WANITA PURNAKRAMA MARANATHA MALANG - Tri Istining Wardani; Asminah Rachmi; Dwi Sudjanarti; Umi Khabibah; Joni Dwi Pribadi; Erma Yanuarni (Jurnal Pengabdian kepada Masyarakat, 2023)
This community service aims to enrich and encourage the entrepreneurial creativity of the target audience in order to empower their skills. Participants in this community service activities are the members of the group of “Purnakrama GSJA - Maranatha Malang”, in which consist of women who are struggling to live alone as widows or unmarried. They live independently and are responsible for their own well-being without the support of a husband or partner. Empowering the participants' skills is delivered by introducing and teaching them the decoupage art technique, that is the art of decorating plain objects/used items with deco-napkins so that the value of the object will increase greatly. After attending this training, participants are expected to stimulate their creativity, as well increase their knowledge and skills, with the result it can be used to help their welfare even though they have to live independently. Decoupage art is chosen a main training topic as it provide a lot of beneficial advantages. Besides it can be easily taught in an efficient time, it also being able to transform used/plain items into more valuable ones because decoupage art have a variety of interesting motifs. Apart from that, the tools and materials used for decoupage art really easy to look for, and the costs are affordable. The competencies have been achieved, as in the end each of the participants has been successfully applied decoupage art technique using two kinds of deco-napkins patterns towards two different medias surfaces, in which each media need special and different treatment to apply decoupage technique. The first media is strap-plastic bag with its rough surface, then another media is flower pot which has smooth surface. In the end, the final evaluation results declared that community service using Decoupage art has been success to empower the members of the group of “Purnakrama GSJA - Maranatha Malang”